Encountering Jesus in the real world of the Gospels - Parker, Cyndi; Cyndi Parker (Peabody, Massachusetts : Hendrickson Publishers, 2021)
"This book focuses on the complexities of the political, social, literary, and religious context of the Gospels. The purpose is to advance readers' understanding of the Gospels and help them encounter Jesus, the disciples, and crowds as real people in a real place at a time vastly different from today"--